A study to assess the pharmacological agent potential of gold nanoparticles and their effects on human cancer cells and hospital pathogens using in vitro methods - Baran, Ayşe (Frontiers in Pharmacology, 2025)
Interest in metal nanoparticles synthesised using green methods is growing steadily. Metal nanoparticles can be synthesised inexpensively and effortlessly using extracts derived from different plants and their diverse components. Gold nanoparticles (Au NPs) were rapidly synthesised from Broccoli (Brassica oleracea L.) agricultural waste using a novel, cost-effective, and eco-friendly method in this work. Analysed data from various techniques including UV-vi, TEM, FESEM, XRD, AFM, FTIR, TGA-DT, EDX, and DLS to assess the properties of the synthesised Au NPs. The characterisation data revealed that the Au NPs had a peak absorbance at 553.10 nm, a surface charge of −19.7 mV, an average hydrodynamic size of 78.75 nm, a monodisperse spherical shape, and were found to be stable. The inhibitory effects of Au NPs with these properties on hospital pathogens and human cancer cells were evaluated by microdilution, disk diffusion and MTT techniquesAs a result of the findings, it was determined that Au NPs have antibacterial, antifungal and anticancer potential as pharmacological agents under in vitro conditions.